Research on China’s New Energy Cross-Provincial Marketization Mechanism Under the Background of “Double Carbon” - Zhou, Qiang; Li, Jin; Lv, Qingquan; Wang, Dingmei; Yang, Shiyou (Frontiers in Energy Research, 2022)
In the past decade, China's new energy has made great achievements, and new energy has become an important main power supply in China. With the promotion of China's power market-oriented reform, market-oriented means has become an important means for China to achieve large-scale and efficient national allocation of new energy. This paper will systematically analyze the design principle of China's new energy cross provincial marketization mechanism, including the design of compound system such as inter provincial medium and long-term transaction and spot transaction, as well as the results achieved, and finally carry out simulation verification.